Hexagonal flake melamine cyanurate and preparation method and application thereof
By preparing hexagonal sheet melamine cyanurate, the mechanical properties and dispersion problems of melamine cyanurate in polymer materials are solved, and the long-lasting flame retardant properties and improved mechanical properties and processing properties of polymer materials are achieved.
Patent Information
- Application Number
- CN202211536541.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-01
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-12-01
AI Technical Summary
The existing melamine cyanurate has a large size, which affects the mechanical properties of polymer materials. The nano-scale products are too small in size and poor powder flowability, resulting in the problems of feeding bridges and uneven dispersion.
Hexagonal sheet melamine cyanurate is used to form a hydrogen bond complex by reacting cyanuric acid with 2-N,N-dimethyl-4-amino-1,3,5-triazine, and then reacting with melamine to prepare a nano-scale product with regular hexagonal sheet morphology.
It significantly reduces the surface free energy of the material, reduces the bonding force between particles, improves the compatibility of flame retardant and polymer matrix, enhances the flame retardant properties of polymer materials, and improves its mechanical properties and processing properties.
Smart Images

Figure CN116003338B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material flame retardants, in particular to a hexagonal flake melamine cyanurate and a preparation method and application thereof. Background Art
[0002] Melamine cyanurate is a flame retardant developed since the 1980s. This type of flame retardant has the advantages of being halogen-free, high in nitrogen content, good in flame retardant efficiency, low in toxicity, environmentally friendly and non-irritating. It is widely used in the flame retardant treatment of polymer composite materials.
[0003] At present, the synthesis of melamine cyanurate is mainly divided into solid phase method and liquid phase method. Among them, the solid phase method is usually to place melamine, cyanuric acid and an appropriate amount of solvent in a solid mixing device such as a mottled force mixer, etc., for mechanical mixing, heating reaction for 3-15 hours, and then dehydrating and drying the material to obtain the product; the liquid phase method is to add melamine and cyanuric acid in an equal molar ratio to a large amount of water or other solvents, and then heat the reaction, filter, wash and dry to obtain a sample. The solid phase method and the liquid phase method essentially use the multiple hydrogen bonds formed between melamine and cyanuric acid to reduce the solubility of the product (hydrogen bond complex) in the solvent. Cyanuric acid (cyanuric acid) can be dissolved in water when heated, while the solubility of melamine in water is relatively small (about 0.33g / 100g water at room temperature), and the solubility of melamine at 100°C is about 5.14g / 100g water. The difference in solubility between cyanuric acid and melamine in water brings many difficulties to the synthesis reaction of melamine cyanurate: (1) unreacted raw materials are prone to saturated precipitation when cooled, especially melamine, which often remains in the product; (2) the reaction rate is affected by solubility, resulting in long reaction time and incomplete reaction; (3) the production process has little room for adjustment. Therefore, although theoretical studies have shown that the final product melamine cyanurate (MCA) has multiple crystallization modes, it is difficult to achieve this in actual production by adjusting temperature, concentration, and addition order.
[0004] CN102532604B discloses a method for preparing large-particle melamine cyanurate by adding polyalkylamide, which is essentially the adhesion effect of the long-chain structure of the polymer; CN102585290 discloses a method for preparing large-particle melamine cyanurate with wide distribution by adding a polymer nucleating agent. However, the melamine cyanurate prepared in the above methods has disadvantages to varying degrees. Large-particle melamine cyanurate and micron melamine cyanurate mainly solve the dispersion problem during extrusion processing. The problem with this type of melamine cyanurate is that the size of melamine cyanurate is large, which greatly affects the mechanical properties of the polymer material; while nano-scale melamine cyanurate has a large specific surface area and high activity. Although it has a better flame retardant effect, it is too small in size and has poor powder fluidity, which often leads to problems such as feeding bridging and uneven dispersion in practical applications.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a hexagonal flake melamine cyanurate with low surface free energy, not easy to agglomerate and easy to disperse.
[0007] The second object of the present invention is to provide a method for preparing hexagonal flake melamine cyanurate, which has simple process, easy operation and high product quality rate.
[0008] The third object of the present invention is to provide an application of hexagonal flake melamine cyanurate, which is easy to disperse in polymer materials, can enhance the flame retardant properties of polymer materials and improve their mechanical properties and processing properties.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] In a first aspect, a hexagonal flake melamine cyanurate.
[0011] Further, the hexagonal flake melamine cyanurate includes nano-scale hexagonal flake melamine cyanurate;
[0012] Preferably, the average particle size of the hexagonal flake melamine cyanurate is below 0.6 μm, preferably 0.2-0.6 μm.
[0013] Furthermore, the water content of the hexagonal flake melamine cyanurate is less than 0.2% by weight;
[0014] Preferably, the residual acid mass content of the hexagonal flake melamine cyanurate is less than 0.2%;
[0015] Preferably, the pH value of the hexagonal flake melamine cyanurate is 7-9.
[0016] In a second aspect, a method for preparing the hexagonal flake melamine cyanurate described in any one of the above items comprises the following steps:
[0017] Cyanuric acid and melamine react under the action of a catalyst to obtain the hexagonal flake melamine cyanurate.
[0018] Further, the catalyst includes 2-N,N-dimethyl-4-amino-1,3,5-triazine;
[0019] Preferably, the solvent for the reaction comprises water.
[0020] Furthermore, the preparation method comprises the following steps:
[0021] Cyanuric acid first undergoes a first reaction with 2-N,N-dimethyl-4-amino-1,3,5-triazine to form a hydrogen bond complex, and then undergoes a second reaction with melamine to obtain the hexagonal flake melamine cyanurate.
[0022] Furthermore, the mass ratio of cyanuric acid to melamine is 1:1;
[0023] Preferably, the mass ratio of 2-N,N-dimethyl-4-amino-1,3,5-triazine to cyanuric acid is 0.05-0.1:1;
[0024] Preferably, the mass ratio of cyanuric acid to water is 1:3-10.
[0025] Further, the temperatures of the first reaction and the second reaction are independently 60-90°C;
[0026] Preferably, the addition of cyanuric acid and melamine each independently comprises batch addition.
[0027] In a third aspect, a use of the hexagonal flake melamine cyanurate described in any one of the above items in flame retardancy of polymer materials.
[0028] Furthermore, the polymer material includes polyamide, polyester and polyolefin.
[0029] Compared with the prior art, the present invention has at least the following beneficial effects:
[0030] The hexagonal flake melamine cyanurate provided by the present invention changes the structural morphology of melamine cyanurate. The melamine cyanurate with regular hexagonal flake morphology has low surface free energy. Therefore, when used as a nano-scale flame retardant material, the surface free energy of the material can be significantly reduced, and the bonding force between material particles can be reduced, thereby avoiding the technical problem of being difficult to disperse during extrusion processing with polymer materials, thereby enhancing the compatibility of the flame retardant with the polymer matrix (not prone to migration and precipitation), so that the polymer has a lasting flame retardant property, and at the same time, the mechanical properties and processing properties of the flame retardant polymer material can be improved.
[0031] The method for preparing hexagonal flake melamine cyanurate provided by the invention has simple process, easy operation and high product quality rate.
[0032] The application of the hexagonal flake melamine cyanurate provided by the present invention is easy to disperse in polymer materials, and can enhance the flame retardant properties of the polymer materials and improve their mechanical properties and processing properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 A reaction diagram of an intermediate formed by the reaction of cyanuric acid and 2-N,N-dimethyl-4-amino-1,3,5-triazine provided in one embodiment of the present invention;
[0035] Figure 2 A reaction diagram of the reaction of an intermediate provided in one embodiment of the present invention with melamine to obtain hexagonal flake melamine cyanurate (MCA product);
[0036] Figure 3 This is a SEM image of the nanoscale regular hexagonal flake melamine cyanurate product obtained in Test Example 1 of the present invention (scale is 2 μm);
[0037] Figure 4 This is a SEM image of the nanoscale regular hexagonal flake melamine cyanurate product obtained in Test Example 1 of the present invention (scale is 10 μm);
[0038] Figure 5 This is a particle size distribution diagram of the nano-scale regular hexagonal flake melamine cyanurate product obtained in Test Example 1 of the present invention;
[0039] Figure 6This is a thermal gravimetric curve of the nanoscale regular hexagonal flake melamine cyanurate product obtained in Test Example 1 of the present invention. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] According to a first aspect of the present invention, a hexagonal flake melamine cyanurate is provided, which can effectively solve the technical problem that melamine cyanurate is easy to agglomerate and difficult to disperse.
[0042] The hexagonal flake melamine cyanurate provided by the present invention changes the structural morphology of melamine cyanurate. The melamine cyanurate with regular hexagonal flake morphology has low surface free energy. Therefore, when used as a nano-scale flame retardant material, the surface free energy of the material can be significantly reduced, and the bonding force between material particles can be reduced, thereby avoiding the technical problem of being difficult to disperse during extrusion processing with polymer materials, thereby enhancing the compatibility of the flame retardant with the polymer matrix (not prone to migration and precipitation), so that the polymer has a lasting flame retardant property, and at the same time, the mechanical properties and processing properties of the flame retardant polymer material can be improved.
[0043] In a preferred embodiment, the hexagonal flake melamine cyanurate of the present invention comprises nano-scale hexagonal flake melamine cyanurate, which has low surface free energy, is not easy to agglomerate, is easy to disperse, and has good compatibility with the polymer matrix.
[0044] The initial decomposition temperature (1% thermal weight loss temperature) of the nano-scale hexagonal flake melamine cyanurate in the present invention is above 350°C.
[0045] In a preferred embodiment, the average particle size of the hexagonal flake melamine cyanurate of the present invention is below 0.6 μm, for example, it can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, and can be further preferably 0.2-0.6 μm, which is more conducive to improving the flame retardant properties, mechanical properties and processing properties of polymer materials as a flame retardant.
[0046] In the present invention, the particle size distribution of the hexagonal flake melamine cyanurate in the range of 1-2 μm can account for more than 95% of the total weight of the product.
[0047] In a preferred embodiment, the water content by mass in the hexagonal flake melamine cyanurate of the present invention is less than 0.2%, the residual acid content by mass is less than 0.2%, and the pH value can be 7-9, for example, 7, 8, 9, but not limited thereto, which is conducive to ensuring the overall performance of the hexagonal flake melamine cyanurate.
[0048] The melamine cyanurate in the particle form with a regular hexagonal sheet structure of the present invention solves the technical problem that when melamine cyanurate is used as a nano-scale material, the material is easy to agglomerate and difficult to disperse due to high surface free energy, too small size and poor fluidity, and achieves the technical effect of significantly reducing the surface free energy of nano-scale melamine cyanurate and weakening the binding force between its particles.
[0049] According to a second aspect of the present invention, there is provided a method for preparing the hexagonal flake melamine cyanurate described in any one of the above, comprising the following steps:
[0050] Cyanuric acid reacts with melamine under the action of a catalyst to obtain hexagonal flake melamine cyanurate.
[0051] The method for preparing hexagonal flake melamine cyanurate provided by the invention has simple process, easy operation and high product quality rate.
[0052] Cyanuric acid in the present invention is also called cyanuric acid, CAS No. 108-80-5, and its structure is as follows:
[0053]
[0054] The melamine in the present invention, CAS No. 108-78-1, has the following structure:
[0055]
[0056] In a preferred embodiment, the solvent used in the reaction of the present invention includes but is not limited to water, which is more conducive to improving the synthesis effect of the product.
[0057] In a preferred embodiment, the mass ratio of cyanuric acid to water can be 1:3-10, for example, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, but not limited thereto, which is more conducive to improving the synthesis effect of the reaction.
[0058] In a preferred embodiment, the catalyst of the present invention includes but is not limited to 2-N,N-dimethyl-4-amino-1,3,5-triazine, CAS No. 4039-98-9, and its structure is as follows:
[0059]
[0060] In a preferred embodiment, the preparation method of the present invention comprises the following steps:
[0061] Cyanuric acid first reacts with 2-N,N-dimethyl-4-amino-1,3,5-triazine to form a hydrogen bond complex (intermediate), see Figure 1 , and then react with melamine for the second time, see Figure 2 , and obtain hexagonal flake melamine cyanurate (MCA product).
[0062] The preparation method provided by the present invention uses 2-N,N-dimethyl-4-amino-1,3,5-triazine, a substance having a structure similar to melamine, as a catalyst. The substance not only has a high solubility in water, but also can react with cyanuric acid to form a hydrogen bond complex. Compared with the direct reaction of melamine with cyanuric acid (also known as cyanuric acid), when cyanuric acid acts with the catalyst 2-N,N-dimethyl-4-amino-1,3,5-triazine, the type and quantity of hydrogen bonds formed are greatly different, which will cause the following effects:
[0063] (1) The reaction mechanism changes: Cyanuric acid and the catalyst 2-N,N-dimethyl-4-amino-1,3,5-triazine are combined in a double hydrogen bond mode to form an intermediate (hydrogen bond complex). When melamine continues to dissolve, melamine will react with the intermediate that has been combined into a complex, replacing the catalyst, thereby forming a cyanuric acid melamine product;
[0064] (2) The crystal form of the product is regulated: the intervention of the catalyst affects the bonding process between melamine and cyanuric acid, making it easier to form melamine cyanuric acid with a regular hexagonal plate morphology;
[0065] (3) The crystal size of the product is affected: the pre-occupancy of the catalyst allows for rapid precipitation in the early stages of the reaction, thereby significantly increasing the number of crystal nuclei. As a result, nanoscale melamine cyanurate particles of uniform size can be obtained without changing the concentration. The surface free energy is significantly reduced, resulting in better dispersibility.
[0066] In a preferred embodiment, the mass ratio of cyanuric acid to melamine may be 1:1, but is not limited thereto, which is more conducive to improving the synthesis effect of hexagonal flake melamine cyanuric acid.
[0067] In a preferred embodiment, the mass ratio of 2-N,N-dimethyl-4-amino-1,3,5-triazine to cyanuric acid can be 0.05-0.1:1, for example, it can be 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, but not limited to this, which is more conducive to improving the synthesis effect of hexagonal flake melamine cyanurate.
[0068] In a preferred embodiment, the temperatures of the first reaction and the second reaction in the present invention can independently be 60-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, but not limited thereto, which is more conducive to fully proceeding the reaction and improving the yield of the product.
[0069] In the present invention, the method of adding melamine includes but is not limited to adding in batches, which is more conducive to improving the synthesis effect of the counter-product and ensuring the yield.
[0070] A typical preparation method of hexagonal flake melamine cyanurate comprises the following steps:
[0071] S1: dissolving cyanuric acid in deionized water, heating to 60-90° C., and keeping the temperature, to obtain a cyanuric acid solution, wherein the mass ratio of cyanuric acid to deionized water is 1:3-10;
[0072] S2: adding a catalyst 2-N,N-dimethyl-4-amino-1,3,5-triazine to the cyanuric acid solution of step S1, mixing, and obtaining a mixed solution, wherein the mass ratio of 2-N,N-dimethyl-4-amino-1,3,5-triazine to cyanuric acid is 0.05-0.1:1;
[0073] S3: adding melamine to the mixed solution of step S2 in three batches according to a mass ratio of melamine to cyanuric acid of 1:1, mixing, and keeping the mixture at a temperature of 60-90° C. for reaction for 2 hours;
[0074] S4: After the reaction in step S3 is completed, the material is discharged and filtered to obtain hexagonal flake melamine cyanurate.
[0075] The method for preparing hexagonal flake melamine cyanurate provided by the invention is not only simple in process and easy to operate, but also has high product quality rate and yield, and is suitable for factory production.
[0076] According to a third aspect of the present invention, there is provided a use of any of the above-mentioned hexagonal flake melamine cyanurate in flame retardancy of polymer materials.
[0077] The hexagonal flake melamine cyanurate of the present invention can be used as an additive flame retardant in the processing and production of polymer material products at the nanometer level. It is not only easy to disperse in the polymer material, but also can enhance the flame retardant performance of the polymer material and improve its mechanical properties and processing performance.
[0078] Flame-retardant materials can be prepared by adding nano-scale regular hexagonal flake melamine cyanurate to polymer materials. The nano-scale regular hexagonal flake melamine cyanurate of the present invention has better dispersibility in polymer materials such as polyamide (PA6, PA66), polyester (PBT, PET, TPU), polyolefin (PE, TPE), etc., and has higher flame retardant efficiency. It can also reduce the influence of the flame retardant on the mechanical strength of the material, and does not affect the coloring of the material products, thereby ensuring that the color of the flame-retardant products is consistent and the injection molded products are colorless.
[0079] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0080] Example 1
[0081] A method for preparing a nanoscale regular hexagonal sheet melamine cyanurate product comprises the following steps:
[0082] 100 L of pure water was added to a 200 L reactor, and then 30 kg of cyanuric acid was added in three batches, heated to 80 ° C, and then 2 kg of catalyst 2-N, N-dimethyl-4-amino-1,3,5-triazine was added, and then 30 kg of melamine was added in three batches, and stirred and kept warm for 2 hours. After the reaction was completed, the material was discharged, filtered, and added to a grinder for graded crushing to obtain a crushed nano-scale regular hexagonal flake cyanuric acid melamine product (performance indicators are shown in Table 1), wherein the mother liquor can be reused for the next reaction.
[0083] Example 2
[0084] A method for preparing a nanoscale regular hexagonal sheet melamine cyanurate product comprises the following steps:
[0085] 100 L of pure water was added to a 200 L reactor, and then 30 kg of cyanuric acid was added in three batches, heated to 80 ° C, and then 3 kg of catalyst 2-N, N-dimethyl-4-amino-1,3,5-triazine was added, and then 30 kg of melamine was added in three batches, and stirred and kept warm for 2 hours. After the reaction was completed, the material was discharged, filtered, and added to a grinder for graded crushing to obtain a crushed nano-scale regular hexagonal flake cyanuric acid melamine product (performance indicators are shown in Table 1), wherein the mother liquor can be reused for the next reaction.
[0086] Example 3
[0087] A method for preparing a nanoscale regular hexagonal sheet melamine cyanurate product comprises the following steps:
[0088] 100 L of pure water was added to a 200 L reactor, and then 30 kg of cyanuric acid was added in three batches, heated to 80 ° C, and then 1.5 kg of catalyst 2-N, N-dimethyl-4-amino-1,3,5-triazine was added, and then 30 kg of melamine was added in three batches, and stirred and kept warm for 2 hours. After the reaction was completed, the material was discharged, filtered, and added to a grinder for graded crushing to obtain a crushed nano-scale regular hexagonal flake cyanuric acid melamine product (performance indicators are shown in Table 1), wherein the mother liquor can be reused for the next reaction.
[0089] Example 4
[0090] A method for preparing a nanoscale regular hexagonal sheet melamine cyanurate product comprises the following steps:
[0091] 100 L of pure water was added to a 200 L reactor, and then 20 kg of cyanuric acid was added in three batches, heated to 80 ° C, and then 2 kg of catalyst 2-N, N-dimethyl-4-amino-1,3,5-triazine was added, and then 20 kg of melamine was added in three batches, and stirred and kept warm for 2 hours. After the reaction was completed, the material was discharged, filtered, and added to a grinder for graded crushing to obtain a crushed nano-scale regular hexagonal flake cyanuric acid melamine product (performance indicators are shown in Table 1), wherein the mother liquor can be reused for the next reaction.
[0092] Example 5
[0093] A method for preparing a nanoscale regular hexagonal sheet melamine cyanurate product comprises the following steps:
[0094] 100 L of pure water was added to a 200 L reactor, and then 20 kg of cyanuric acid was added in three batches, heated to 80 ° C, and then 1 kg of catalyst 2-N, N-dimethyl-4-amino-1,3,5-triazine was added, and then 20 kg of melamine was added in three batches, and stirred and kept warm for 2 hours. After the reaction was completed, the material was discharged, filtered, and added to a grinder for graded crushing to obtain a crushed nano-scale regular hexagonal flake cyanuric acid melamine product (performance indicators are shown in Table 1), wherein the mother liquor can be reused for the next reaction.
[0095] Example 6
[0096] A method for preparing a nanoscale regular hexagonal sheet melamine cyanurate product comprises the following steps:
[0097] 100 L of pure water was added to a 200 L reactor, and then 10 kg of cyanuric acid was added in three batches, heated to 80 ° C, and then 1 kg of catalyst 2-N, N-dimethyl-4-amino-1,3,5-triazine was added, and then 10 kg of melamine was added in three batches, and stirred and kept warm for 2 hours. After the reaction was completed, the material was discharged, filtered, and added to a grinder for graded crushing to obtain a crushed nano-scale regular hexagonal flake cyanuric acid melamine product (performance indicators are shown in Table 1), wherein the mother liquor can be reused for the next reaction.
[0098] Example 7
[0099] A method for preparing a nanoscale regular hexagonal sheet melamine cyanurate product comprises the following steps:
[0100] 100 L of pure water was added to a 200 L reactor, and then 10 kg of cyanuric acid was added in three batches, heated to 80 ° C, and then 0.5 kg of catalyst 2-N, N-dimethyl-4-amino-1,3,5-triazine was added, and then 10 kg of melamine was added in three batches, and stirred and kept warm for 2 hours. After the reaction was completed, the material was discharged, filtered, and added to a grinder for graded crushing to obtain a crushed nano-scale regular hexagonal flake cyanuric acid melamine product (performance indicators are shown in Table 1), wherein the mother liquor can be reused for the next reaction.
[0101] Example 8
[0102] A method for preparing a nanoscale regular hexagonal sheet melamine cyanurate product comprises the following steps:
[0103] 100 L of pure water was added to a 200 L reactor, and then 30 kg of cyanuric acid was added in three batches, heated to 90 ° C, and then 3 kg of catalyst 2-N, N-dimethyl-4-amino-1,3,5-triazine was added, and then 30 kg of melamine was added in three batches, and stirred and kept warm for 2 hours. After the reaction was completed, the material was discharged, filtered, and added to a grinder for graded crushing to obtain a crushed nano-scale regular hexagonal flake cyanuric acid melamine product (performance indicators are shown in Table 1), wherein the mother liquor can be reused for the next reaction.
[0104] Comparative Example 1
[0105] A method for preparing a nano-scale melamine cyanurate product comprises the following steps:
[0106] 100 L of pure water was added to a 200 L reactor, and then 30 kg of cyanuric acid was added in three batches, and the mixture was heated to 80°C. Then 30 kg of melamine was added in three batches, and the mixture was stirred and kept warm for 2 hours. The mixture was discharged, filtered, and added to a grinder for graded crushing to obtain a crushed melamine cyanurate product (performance indicators are shown in Table 1).
[0107] Table 1
[0108] Example purity(%) 1% thermal weight loss temperature (℃) Surface pH Residual acid mass content (%) Average particle size D50 (μm) Example 1 98.7 336 7.8 0.02 0.54 Example 2 99.1 348 8.2 0.12 0.34 Example 3 98.8 358 8.6 0.17 0.22 Example 4 99.4 343 7.8 0.08 0.23 Example 5 99.2 358 8.5 0.07 0.37 Example 6 99.4 352 8.4 0.12 0.25 Example 7 99.1 355 7.7 0.01 0.40 Example 8 98.9 357 8.1 0.12 0.39 Comparative Example 1 95.3 313 4.6 0.7 4.65
[0109] It can be seen from the data in Table 1 that the purity of the nanoscale regular hexagonal melamine cyanurate obtained by the preparation method of the present invention is ≥98%, the thermal weight loss temperature is ≥330°C, the surface pH value is ≥7, the residual acid mass content is ≤0.2%, and the average particle size D50 is ≤0.6μm. Many properties exceed those of the ordinary melamine cyanurate product obtained by the preparation method of Comparative Example 1.
[0110] It can be seen that the nanoscale regular hexagonal sheet melamine cyanurate product prepared by the present invention using 2-N,N-dimethyl-4-amino-1,3,5-triazine as a catalyst can reduce its own hydrogen bonding effect and prevent traditional melamine-cyanuric acid molecules from self-assembling to form a large planar hydrogen bond network, so it has the characteristics of good dispersion, high thermal stability and high flame retardant efficiency.
[0111] Test Example 1
[0112] The average particle size of the nano-scale regular hexagonal flake melamine cyanurate product provided in Examples 1-8 of the present invention is between 0.2 and 0.6 μm, wherein the particle size distribution in the range of 1-2 μm accounts for more than 95% of the product weight. Figure 3 , Figure 4 as well as Figure 5 ,in, Figure 5 It is a particle size distribution diagram, the horizontal axis is the particle size (μm), and the vertical axis is the differential distribution (%).
[0113] The thermogravimetric curve of the nanoscale regular hexagonal flake melamine cyanurate product provided in Example 3 of the present invention is shown in FIG. Figure 6 , where the horizontal axis is temperature (°C) and the vertical axis is weight loss (%). It can be seen that the initial decomposition temperature of nanoscale regular hexagonal flake melamine cyanurate is above 350°C.
[0114] Test Example 2
[0115] The nanoscale regular hexagonal melamine cyanurate products provided in Examples 1-8 and the ordinary melamine cyanurate product provided in Comparative Example 1 were added to nylon 66 (PA66) as flame retardants, respectively, to obtain flame retardant PA66 (respectively referred to as flame retardant PA66 Examples 1-8 and flame retardant PA66 Comparative Example 1). The various properties of the flame retardant PA66 were then tested, and the results are shown in Table 2.
[0116] Among them, the formula of flame retardant PA66 and the extrusion process are as follows:
[0117] The formula includes the following components by mass fraction:
[0118]
[0119] Extrusion process: After the components are mixed, they are extruded into materials through a Φ36 twin-screw extruder with an extrusion temperature of 220-270°C and a rotation speed of 300rpm.
[0120] The dispersion grade test in Table 2: Flame retardant PA66 is pressed into 0.1-0.2mm thin sheets in a tablet press, and then observed against light to see if there are dispersed powder packets. The score is judged on a scale of 0-10, with 0 being no powder packets, 1-2 being slight, 3-4 being obvious, 5 being more common, and 10 being the most.
[0121] Table 2
[0122]
[0123] It can be seen from the data in Table 2 that the dispersion performance of the nano-scale regular hexagonal flake melamine cyanurate is better than that of the ordinary melamine cyanurate. The nano-scale regular hexagonal flake melamine cyanurate of the present invention can be dispersed more quickly and evenly during the combustion process of the polymer material, and the blowing is more uniform, thereby improving the flame retardant performance of the material and having good thermal stability.
[0124] Test Example 3
[0125] The nanoscale regular hexagonal flake melamine cyanurate products provided in Examples 1-8 and the ordinary melamine cyanurate product provided in Comparative Example 1 were added to PBT (polybutylene terephthalate) as flame retardants, respectively, and flame retardant PBT was obtained accordingly (respectively referred to as flame retardant PBT Examples 1-8 and flame retardant PBT Comparative Example 1). The various properties of the flame retardant PBT were then tested, and the results are shown in Table 3.
[0126] Among them, the formula of flame retardant PBT and the extrusion process are as follows:
[0127] The formula includes the following components by mass fraction:
[0128]
[0129] Extrusion process: After the components are mixed, they are extruded into materials through a Φ36 twin-screw extruder with an extrusion temperature of 220-240°C and a rotation speed of 40rpm.
[0130] Table 3
[0131]
[0132] Test Example 4
[0133] The nanoscale regular hexagonal flake melamine cyanurate products provided in Examples 1-8 and the ordinary melamine cyanurate product provided in Comparative Example 1 were added to PE (polyethylene) as flame retardants, and flame-retardant PE (respectively referred to as flame-retardant PE Examples 1-8 and flame-retardant PE Comparative Example 1) were obtained accordingly. The various properties of the flame-retardant PE were then tested, and the results are shown in Table 4.
[0134] Among them, the formula of flame retardant PE and the extrusion process are as follows:
[0135] The formula includes the following components by mass fraction:
[0136]
[0137] Extrusion process: After the components are mixed, they are extruded into materials through a Φ36 twin-screw extruder with an extrusion temperature of 130-180°C and a rotation speed of 40rpm.
[0138] Table 4
[0139]
[0140] From the data recorded in Table 2, Table 3 and Table 4, it can be seen that when the nanoscale regular hexagonal flake melamine cyanurate product of the present invention is used as a flame retardant in polymer materials such as polyamide (PA6, PA66), polyester (PBT, PET, TPU) and polyolefin (PE, TPE), it can significantly improve the various mechanical properties of flame retardant polymer materials, such as tensile and bending resistance.
[0141] In summary, the nanoscale regular hexagonal flake melamine cyanurate product of the present invention has good compatibility with polymer materials such as polyamide (PA6, PA66), polyester (PBT, PET, TPU) and polyolefin (PE, TPE), has better dispersibility in polymer materials, and has higher flame retardant efficiency. At the same time, it can reduce the influence of flame retardants on the mechanical strength of polymer materials, and can also be used in black and bright flame retardant nylon products without affecting the coloring of the products, ensuring that the color of the flame retardant products is consistent and the injection molded products are free of color spots.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing hexagonal flake melamine cyanurate, characterized in that: The following steps are involved: S1: dissolving cyanuric acid in deionized water, heating to 60-90° C., and keeping the temperature, to obtain a cyanuric acid solution, wherein the mass ratio of cyanuric acid to deionized water is 1:3-10; S2: adding a catalyst 2-N,N-dimethyl-4-amino-1,3,5-triazine to the cyanuric acid solution of step S1, mixing, and obtaining a mixed solution, wherein the mass ratio of 2-N,N-dimethyl-4-amino-1,3,5-triazine to cyanuric acid is 0.05-0.1:1; S3: adding melamine to the mixed solution of step S2 in three batches according to a mass ratio of melamine to cyanuric acid of 1:1, mixing, and keeping the mixture at a temperature of 60-90° C. for reaction for 2 hours; S4: After the reaction in step S3 is completed, the material is discharged and filtered to obtain hexagonal flake melamine cyanurate.
2. The preparation method according to claim 1, characterized in that: The hexagonal flake melamine cyanurate is nano-scale hexagonal flake melamine cyanurate.
3. The preparation method according to claim 1, characterized in that: The average particle size of the hexagonal flake melamine cyanurate is less than 0.6 μm.
4. The preparation method according to claim 3, characterized in that: The average particle size of the hexagonal flake melamine cyanurate is 0.2-0.6 μm.
5. The preparation method according to claim 1, characterized in that: The water content of the hexagonal flake melamine cyanurate is less than 0.2% by weight; The residual acid mass content of the hexagonal flake melamine cyanurate is less than 0.2%; The pH value of the hexagonal flake melamine cyanurate is 7-9.
Citation Information
Patent Citations
Preparation method of melamine cyanurate with large particle size
CN102532604B
High stack-density sheet structural melamine cyanurate and production method and application for flame-resistant material
CN101037417A
Method for preparing nano melamine cyanurate acid (MCA)
CN101914220A
Preparation method for melamine cyanurate nanosheet microsphere and application thereof
CN110317181A
Preparation method of high-dispersion melamine cyanurate flame retardant
CN114751869A
Cited By
Multifunctional fireproof flame-retardant coating for new energy battery and preparation method of multifunctional fireproof flame-retardant coating
CN121825357A